IMPLEMENTASI SISTEM INFORMASI MANAJEMEN PROGRAM KERJA BERBASIS WEB SERVER STUDI KASUS DI KANTOR CAMAT SYIAH KUALA - Fadhlon, Fadhlon (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2014)
Subdistrict Office Syiah Kuala is one sub-district office located in Banda Aceh. Each sub-district office has a work program established by the secretariat of the region annually. The wo rk program includes programs and activities, duties and innovation. Activities and the contributions of the work program had the same progress in the form of physical realization. The work program in the form of activity has a physical realization and realization figures to be achieved in each year that must be managed by each unit section. Progress of the work program is very important to know to be reported to the local government as the evaluation and monitoring of the work program has been established. With the situation is necessary to design a work program management data maintained in order to become more efficient and accurate. System design in the making of this information system is developed by using some software that XAMPP 1.7.9, editor Notepad ++, PHP and MySQL. System design methods are used to identify the components of the information system design includes the design ERD, DFD, Flowchart, and the structure of the database table. With the work program of management information systems at sub-district office Syiah Kuala this, the sub can monitor, evaluate and assess the progress of the work program which has been assigned to each unit section in more detail, quickly and accurately so that the district head can determine the extent of realization of the budget numbers in each -masing activities in order to be a reference as decision makers.Keywords: Information Systems, Program Management, Kuala Syiah Head Office ,PHP &